2017
DOI: 10.1371/journal.pgen.1006948
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the Candida albicans biofilm transcription factor network using simple and complex haploinsufficiency

Abstract: Biofilm formation by Candida albicans is a key aspect of its pathobiology and is regulated by an integrated network of transcription factors (Bcr1, Brg1, Efg1, Ndt80, Rob1, and Tec1). To understand the details of how the transcription factors function together to regulate biofilm formation, we used a systematic genetic interaction approach based on generating all possible double heterozygous mutants of the network genes and quantitatively analyzing the genetic interactions between them. Overall, the network is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(88 citation statements)
references
References 48 publications
(121 reference statements)
4
81
3
Order By: Relevance
“…Our initial studies in this area indicate that specific TFs work with others and that these relationships are dynamic [10]. As demonstrated by our CHI experiments [10,21] and the double mutant array approach of Shapiro and colleagues [9], modestly sized, focused arrays of strains containing systematic deletions of pairs of genes with previously characterized functions can provide new insights into genetic network function without recourse to large scale sets of mutant arrays. Thus, genetic interaction analysis does not need to be genome wide to be informative.…”
Section: Beyond Single Gene Analysis In C Albicansmentioning
confidence: 83%
See 3 more Smart Citations
“…Our initial studies in this area indicate that specific TFs work with others and that these relationships are dynamic [10]. As demonstrated by our CHI experiments [10,21] and the double mutant array approach of Shapiro and colleagues [9], modestly sized, focused arrays of strains containing systematic deletions of pairs of genes with previously characterized functions can provide new insights into genetic network function without recourse to large scale sets of mutant arrays. Thus, genetic interaction analysis does not need to be genome wide to be informative.…”
Section: Beyond Single Gene Analysis In C Albicansmentioning
confidence: 83%
“…If a double homozygous mutant is constructed with such a TF, then only positive genetic interactions will be measurable. We and others have shown that double heterozygous mutants can be used to identify genetic interactions by virtue of a phenomenon called complex haploinsufficiency (CHI) [10,21].…”
Section: Complex Haploinsufficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…Haploinsufficiency has been extensively used by Krysan and colleagues to quantitate genetic interactions in C. albicans [84][85][86][87][88]. This includes the examination of strains both for simple haploinsufficiency (observable phenotypes in strains heterozygous for a single gene) and for complex haploinsufficiency (phenotypes in strains heterozygous for two different genes).…”
Section: Loh Is Frequent In C Albicansmentioning
confidence: 99%